(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2021)
This article analyses how the Chilean Public Administration has been laid down in the Constitutions of 1833, 1925 and 1980. The main issues examined are the presidentialism, the institutional rigidity, public employment based on merit and centralism. The second part focuses on several failed attempts at innovation, such as the territorial decentralization or the professionalization of public employment. Finally, it makes some recommendations for the constitution- making process.